ANALYSIS OF HOUSEHOLD INCOME AND EXPENDITURES OF RED CHILLIA FARMERS IN SAWANG DISTRICT ACEH UTARA REGENCY - Riani, Riani; Adhiana, Adhiana; Martina, Martina; Ariani, Rita (CV. Radja Publika, 2022)
One of the vegetable crops that have high economic value and is always needed is red chili. Red chili farming in Sawang District is an activity of farmer households in obtaining income to meet household consumption needs in the form of food and non-food. The ability of farmers to obtain income that is used for household consumption will determine the level of welfare of red chili farmers' households. The purpose of this study was to analyze the household income and expenditure of red chili farmers in Sawang District, North Aceh Regency with a total sample of 40 families. Data were analyzed by quantitative descriptive method. The results showed that the household income of farmers came from agricultural and non-agricultural income with the total income of all respondents amounting to 62,523,981.25 IDR /production process or 10,420,663.54 IDR/month. The income is used to meet food and non-food needs in the amount of 3,579,227 IDR/month. Meanwhile, the welfare level of farmer households is low based on the income structure and expenditure structure.